Environmental effects on genetic variation of chilling resistance in cucumber - Smeets, L; Wehner, T.C (Euphytica, 1997)
Environmental effects on genetic variation for chilling resistance were studied in nine cultivars and breeding lines (referred to as cultigens hereafter) of cucumber (Cucumis sativus L.). Five experiments were carried out in controlled-environment chambers to measure the effects of growth temperature, photoperiod, duration of chilling, light level during chilling, and watering frequency on chilling resistance of seedlings at the cotyledon and first true leaf growth stages. Significant interactions were found between cultigen and all environmental factors studied except for the photoperiod and watering frequency. Cultigen rank was affected by growth temperature before chilling, chilling duration, and light level during chilling, but shifts in rank were not consistent. Genetic variation was largest when the plants were grown at 22/18 °C, most pronounced after a chilling duration of 5 to 9 hours and a light level during chilling of 270 µmol·m^sup -2^·s^sup -1^. Variation was larger at the first true leaf stage than at the cotyledon stage. Differences among cultigens in chilling damage were largest 5 days after chilling. Therefore, it seems that testing for genetic variation in chilling damage can be restricted to one set of environmental conditions. We recommend the following conditions for screening cucumber for genetic variation in chilling resistance: grow the plants at 22/18 °C, under a 9-hour photoperiod with a 3-hour night interruption, water them once daily, subject them at the first true leaf stage to a chilling treatment of 7 hours at 4°C at a light level of 270 µmol·^sup -2^·s^sup -1^, and evaluate damage 5 days after treatment.[PUBLICATION ABSTRACT]